RECORDED TEACHER MODEL VIDEO LESSON IN DEVELOPING THE LETTER SOUND RECOGNITION SKILL OF KINDERGARTEN LEARNERS - TAMANU, REYMALYN (International Journal of Arts, Sciences and Education, 2021)
This action study was carries out to develop the letter sound identification abilities of kindergarten pupils of San Isidro Elementary School, Buguey North District during the school year 2020-2021 using a Recorded Teacher Model Video Lesson. Furthermore, this action research answered the following research questions: 1. what is the pre-test and the post-test score of the participants before and after the implementation of the Recorded Teacher Model Video Lesson? 2. Is there a significant difference on the pre-test and post-test score of the participants using the Recorded Teacher Model Video? 3. What is the effect size of using Recorded Teacher Model Video Lesson in developing the letter sound recognition skill of the participants? 4. What is the intervention plan that can be proposed to sustain the utilization of the innovation/intervention?” The recipient of this study is composed of 29 kindergarten pupils (10 male and 9 female) as participants from San Isidro Elementary School, Buguey North District using total enumeration. The research made use pretest and posttest. The data was collected using an experimental design and processed and analyzed using mean, frequency, t- test, and Eta square. The findings of this research show how beneficial Recorded Video is in helping the kindergarten pupils at San Isidro Elementary School. The mean percentage score of has increased significantly. There is a significant difference between the subjects’ pretest and post-test mean scores, and the eta2 indicates that the Recorded Video is an effective intervention in developing kindergarten pupils’ letter sound identification abilities. As a result, the researcher advised that the Kindergarten Teachers employ the intervention to help kindergarten pupils strengthen their letter sound identification abilities. Collaboration with administrators and educators is required for the implementation of the intervention, which should be prioritized to include and develop the usage of Recorded Teacher Model video. For the continuity and enhancement of this action research, the following suggestions and recommendations intended for this study must be done and put into action. As conclusion, the Recorded Teacher Model Video Lesson was effective intervention in developing pupil’s performance in letter sound recognition. Hence, it was recommended that this intervention was utilized in kindergarten classes and that teachers should master varying techniques thru this intervention to better attain the learners letter sound recognition skill.